2009
DOI: 10.1007/s10532-009-9249-z
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic biodegradation of the brominated flame retardants, dibromoneopentyl glycol and tribromoneopentyl alcohol

Abstract: Halogenated organic compounds constitute one of the largest and most diverse groups of chemicals in the environment. Many of these compounds are toxic, persistent and, as a result of their often limited biodegradability, tend to bioaccumulate in the environment. Dibromoneopentyl glycol (DBNPG) and tribromoneopentyl alcohol (TBNPA) are brominated flame retardants commonly used as additives during the manufacture of plastic polymers and as chemical intermediates in the synthesis of other flame retardants. Both a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 29 publications
2
13
0
Order By: Relevance
“…The peak identified as HBCD elutes in the region where the hexa-BDEs elute, similar to the elution order previously reported by Korytár et al (2002) [10]. Tribromoneopentyl alcohol is a reactive BFR used in the synthesis of high molecular-weight flame retardants and as an additive in the manufacturing of polymers [41].…”
Section: Identification Of Ohcssupporting
confidence: 86%
“…The peak identified as HBCD elutes in the region where the hexa-BDEs elute, similar to the elution order previously reported by Korytár et al (2002) [10]. Tribromoneopentyl alcohol is a reactive BFR used in the synthesis of high molecular-weight flame retardants and as an additive in the manufacturing of polymers [41].…”
Section: Identification Of Ohcssupporting
confidence: 86%
“…It was found that TBNPA could be decomposed by a sequence of reactions that form 3,3-bis(bromomethyl)oxetane, 3-bromomethyl-3-hydroxymethyloxetane, and 2,6-dioxaspiro[3.3]-heptane (DOH), releasing one bromide ion at each stage (Ezra et al, 2005). Segev et al (2009) have experimentally confirmed that TBNPA can undergo microbiological degradation and that the process can be facilitated in order to improve treatment of ground water.…”
Section: B R O H B R B Rmentioning
confidence: 99%
“…It is heavily used as a flame retardant in urethane foam, but little to no information was previously available concerning its potential to induce toxicity [ 38 ]. DBNPG did not induce mortality or malformations in this model, and very little research has been conducted on this chemical, with most focusing on the biodegradation [ 39 ].…”
Section: Discussionmentioning
confidence: 99%